The effect of seasonal variation on macromineral contents of sainfoin genotypes and assessments with biplot analysis - Sayar, Mehmet Salih; Han, Yavuz (Progress in Nutrition, 2023)
The use of quality forages in animal nutrition will make great contribution to increase in animal products both in quantity and quality. Macromineral content is an important factor affecting the quality of forages, and the contents in forages can vary due to many factors. Seasonal variation is one of the among the factors, and the study was held to reveal the effect of spring and autumn seasons cuttings on macromineral contents of sainfoin (Onobrychis viciifolia Scop.) which is one of the important and mostly cultivated perennial legume forage species in Turkey. For this reason; a field experiment was conducted according to randomized blocks design with three replications. The study results showed that there were highly significant differences (P<0.01) between the cutting seasons in terms all of the examined traits, and calcium (Ca), potassium (K), magnesium (Mg) and phosphorus (P) contents forages of sainfoin genotypes in autumn season were found lower than those of in the spring season cutting. Moreover, by taking into to all of the examined traits together, biplot analysis revealed that Lütfibey and Peschanjy-1251 cultivars came to fore in spring season cutting, while CTC Population and Ozerbey-03 cultivars came to fore in autumn season cutting. Also, sainfoin forage obtained in spring season cutting was found richer in terms of Ca, Mg, P and K contents, but due to higher K/(Ca+Mg) (tetany) ratio of the spring season, animal feed with the spring season sainfoin forage may be more susceptible to catching grass tetany incidence especially for dairy cows. To avoid risk of the incidence, the feeds having more Mg content and lower K content should be taken place in the animal rations.